The Modernization Process of Conservative Female Identity Via Body and Aesthetics: The Âlâ Magazine - Sağır, Adem (Journal of History Culture and Art Research, 2018)
The fundamental argument of the present study was that the conservative female identity was based on the regeneration of body within modern and capitalistic context. The concept of body was focused on because it referred to a context included in interest of power, and it could be reconstructed forms again and again in an observable manner. The present study examined the “ÂLÂ” Magazine that had been published for one year. The main reason for the selection of the “ÂLÂ” Magazine was that it reflected the modernization process of the conservative female identity. In addition, the present study intended to demonstrate how the Magazine represented the stage which the conservative female identity had reached in participating in the public life after the 1980s. A distinctive characteristic of the ÂLÂ Magazine is that it attempts to make the perception of “manhood opening a space for themselves by using political power” – a frequently constructed perception in the conservative tradition – inconsistent with the spaces they open for themselves. According to the present study, the conservative female image bears neo-conservative and neo-capitalistic traces while the conservative female identity tries to take itself out of the male power within the triplet of aesthetics, admiration, and beauty.